Characteristics of medium‐scale traveling ionospheric disturbances observed near the Antarctic Peninsula by HF radar. Issue 9 (5th September 2013) - Grocott, A.; Hosokawa, K.; Ishida, T.; Lester, M.; Milan, S. E.; Freeman, M. P.; Sato, N.; Yukimatu, A. S.
Abstract : [1] We present a survey of medium‐scale traveling ionospheric disturbances (MSTIDs) observed by a Super Dual Auroral Radar Network HF radar located in the Falkland Islands between May 2010 and April 2011. The radar has a field of view that overlooks the Antarctic Peninsula, a known hot spot of gravity wave activity. We present observations of radar ground‐backscatter data, in which the signatures of MSTIDs are manifested as structured enhancements in echo power. Observed periods were in the range 30–80 min, corresponding to frequencies of 0.2–0.6 mHz. Wavelengths were generally in the range 200–800 km and phase speeds in the range 100–300 m s −1 . These values are within the ranges typically associated with medium‐scale gravity waves. We find a primary population of northward (equatorward) propagating MSTIDs, which demonstrate an association with enhanced solar wind‐magnetosphere coupling and a smaller, westward propagating population, that could be associated with atmospheric gravity waves excited by winds over the Andean and Antarctic Peninsula mountains or by the high winds of the Antarctic Polar Vortex. Key Points: Two populations of MSTIDs were observed near to the Antarctic Peninsula The main population propagates equatorwards from an apparent auroral source A small population, related to AGWs of tropospheric origin, propagate westward